Synthesis of Zataria Multiflora extraction loaded chitosan/PEO nanofibers via electrospinning method for potential biomedical applications - elham karimi; minoo sadri; motahare hosseini; Ali heidari; Samane kargar-ghalesefi; Zeinab Krimimoghadam (Fasa University of Medical Sciences, 2018)
Background & Objective: The nanofibers are referred to as fibers with a diameter of less than 1000 nm. There are various ways to make nanofibers, one of which is electrospinning. In this method, nanofibers are formed on aluminum sheets. The conversion of chitosan to derivatives with greater solubility, its mixing with other polymers and the use of special solvents are methods for its ease of use. In this study, antimicrobial thyme extracts were prepared for the synthesis of chitosan / polyethylenoxide and thyme nanofibers by electroporation. Materials & methods: Using electrospinning, chitosan and polyethylenoxide were prepared Ratio of 90 to 10 and 80% tween in a 0.5 molar acetic acid solution. Thyme extract was added and after the synthesis of nanofibers, images of SEM were taken, then the diameter of the nanofibers with clemex vision software was measured. Results: According to the scanning electron microscopy (SEM) images and the nanofibers diameter obtained from the solution with chitosan / polyethylenoxide / thyme formulation with Ratio of 90 to 10, the mean diameter of nanofibers was in the range of 100-60 nm (best fiber with the lowest node). Conclusion: Prepared nanofibers are widely used in the medical industry, especially in the field of tissue engineering and wound scaffolds and also are used as antibacterial candidate. In addition to being effective in wound healing, they also reduce the cost of treatment.